Unconventional mitigation: Carbon dioxide removal as a new approach in EU climate policy - Oliver Geden; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2020)
If the EU wants to achieve net zero emissions by 2050, enacting conventional climate change mitigation measures to avoid emissions of greenhouse gases will not be enough. To compensate for unavoidable residual emissions, unconventional measures to remove CO2 from the atmosphere will also be necessary - for example, through afforestation or the direct capture of CO2 from ambient air. Not all member states and economic sectors will have achieved greenhouse gas neutrality by 2050; some will already need to be below zero by then. The option of CO2 removal from the atmosphere will allow greater flexibility in climate policy, but will also raise new distributional issues. Avoiding greenhouse gas emissions should be given political priority over the subsequent removal of CO2. Net zero targets should be explicitly divided into emission reduction targets and removal targets, instead of simply offsetting the effects of both approaches. The future development of an EU CO2 removal policy should be structured by adequate policy design. Whether the EU chooses a proactive or cautious entry pathway in the medium term will depend not least on the net negative targets it assumes for the period after 2050. In the coming years, the EU should focus on investing more in research and development of CO2 removal methods and gaining more practical experience in their use. Only if the EU and its members actually succeed in convincingly combining conventional emission reductions and unconventional CO2 removals to reach net zero will the EU be able to live up to its status as a pioneer in climate policy.
Keywords: 320; Schadstoffemission; Reduzierung/Rückgang; Kohlendioxid-Abscheidung und -Lagerung; Walderhaltung/Aufforstung; Meeresbiologie